Jeopardy game in teaching report text - Siti Trisna Dewi (Concept : Community Concern for English Pedagogy and Teaching, 2018)
Abstract This study attempts to explain how the implementation of jeopardy game in teaching report text, and try to find the strengthnesses and the weaknesses in jeopardy game when implemented in teaching report text. MAN 1 Kota Cirebon was chosen as the place to conduct this study. This study used qualitative case study as methods of the study. A total of 33 students of class X MIPA 2 became participants consist of 13 male students and 20 female students. To obtain data, the writer used classroom observation to find out how the implementation of jeopardy game in the classroom. And to find out the strengthnesses and the weaknesses jeopardy game, the writer used interviews with student representatives from each group. There were 6 students to be interviewed. And the results of the study, the writer explain that the game jeopardy is considered successful because all students can follow the rules in jeopardy game when implemented. The writer also found four strengthnesses and two weaknesses in implementing jeopardy game. The conclusion of this study are Jeopardy Game is considered successful when implemented in tenth grade science two of MAN 1 Kota Cirebon. And the writer find out four strengthness and two weaknesses of Jeopardy Game in teaching report text. Suggestion of this study are Jeopardy Game more suitable implemented in small class or language center, and there is no research about Jeopardy Game implemented in teaching English except about reading comprehenshion. Keywords: Jeopardy game; Reading Comprehenshion